Coordinated Development of Urban Land Use and Ecological Economics in China - Zhiyuan Zhu; Gang Du (Journal of Mathematics)
To analyze the coordination between land use and the ecological economy in China, ecoefficiency and land use intensity were measured using the nonradial, nonoriented slacks-based measure (SBM) and the vertical and horizontal scatter degree method. The TOPSIS method was then used to comprehensively evaluate regional differences in coordination. Our research indicates that the level of coordinated development between intensive urban land use and the ecological economy in China showed an overall upward trend from 2006 to 2017. The level of coordination was high in Beijing, Shanghai, and Tianjin and was low in Gansu, Ningxia, and Xinjiang. Changes in ecoefficiency were not consistent with the degree of coordination, and intensive urban land use was positively correlated with the level of coordination, which showed a mutually reinforcing relationship. Improving ecoefficiency is necessary for intensive urban land use, and for ecological improvement, coordinated development between ecoefficiency and urban land use intensity is essential. The establishment of environmentally friendly land use patterns could promote urban land use.